Arousal electrical stimuli evoke sudomotor activity related to P300, and skin vasoconstrictor activity related to N140 in humans. Issue 5 (May 2015) - Kuwahara, Yuko; Tsukahara, Reiko; Iwase, Satoshi; Shimizu, Yuuki; Nishimura, Naoki; Sugenoya, Junichi; Sato, Motohiko
Highlights Skin sympathetic nerve activity (SSNA) contained sudomotor and skin vasoconstrictor activities is modulated not only by thermal conditions, but also arousal stimuli. We elucidated that different components of event-related potentials (ERPs) are related to sudomotor and vasoconstrictor activities composing arousal SSNA bursts. The sudomotor activity in arousal SSNA is related to attention and the skin vasoconstrictor activity is related to the detection of somatosensory events.